Defending the state from digital Deceit: the reflexive securitization of deepfake. Issue 1 (1st January 2021) - Taylor, Bryan C.
ABSTRACT: Recent revelation of disinformation campaigns conducted by external adversaries on social media platforms has triggered anxiety among western liberal democracies. One focus of this anxiety has been the emerging technology known as deepfake . In examining related controversy, I use the theoretical lens of securitization to establish how communicative reflexivity shapes the attribution of threat to digital media. Next, focusing on the case of the U.S. government, I critique deepfake's securitization by applying two theories of media and state (in-) security. I argue that deepfake sustains the liberal state's conventional dread of mimetic threats posed to its ontological security . I then challenge this narrative by exploring satire as an alternate configuration of deepfake's capabilities. I conclude by summarizing the implications of this case for ongoing study of digital media, conflict, and politics.